SOURCES OF ACCIDENTS IN PHYSICAL EDUCATION AND SPORTS ACTIVITY - CIORBĂ Constantin; MOROŞAN LARIONESCU Virgil (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
The present study is about identifying and classifying the sources of accidents in physical education and sports activity. This article does not describe all types of accidents (an impossible thing to do in the present paper), but it rather reflects the sources of accidents and the so - called risk - factors which can be easily identified by all the specialists in the continuous fight for "primum non noccere".